Transcriptional dysregulation in developing trigeminal sensory neurons in the LgDel mouse model of DiGeorge 22q11.2 deletion syndrome. (12th February 2020) - Maynard, Thomas M; Horvath, Anelia; P Bernot, James; Karpinski, Beverly A; Tavares, Andre L P; Shah, Ankita; Zheng, Qianqian; Spurr, Liam; Olender, Jacqueline; Moody, Sally A; Fraser, Claire M; LaMantia, Anthony-S; et al.
Abstract: LgDel mice, which model the heterozygous deletion of genes at human chromosome 22q11.2 associated with DiGeorge/22q11.2 deletion syndrome (22q11DS), have cranial nerve and craniofacial dysfunction as well as disrupted suckling, feeding and swallowing, similar to key 22q11DS phenotypes. Divergent trigeminal nerve (CN V) differentiation and altered trigeminal ganglion (CNgV) cellular composition prefigure these disruptions in LgDel embryos. We therefore asked whether a distinct transcriptional state in a specific population of early differentiating LgDel cranial sensory neurons, those in CNgV, a major source of innervation for appropriate oropharyngeal function, underlies this departure from typical development. LgDel versus wild-type (WT) CNgV transcriptomes differ significantly at E10.5 just after the ganglion has coalesced. Some changes parallel altered proportions of cranial placode versus cranial neural crest-derived CNgV cells. Others are consistent with a shift in anterior–posterior patterning associated with divergent LgDel cranial nerve differentiation. The most robust quantitative distinction, however, is statistically verifiable increased variability of expression levels for most of the over 17 000 genes expressed in common in LgDel versus WT CNgV. Thus, quantitative expression changes of functionally relevant genes and increased stochastic variation across the entire CNgV transcriptome at the onset of CN V differentiation prefigure subsequent disruption of cranial nerve differentiation and oropharyngeal function in LgDel mice.